사람Tyrosine Hydroxylase promoter에 의해 형광단백질을 발현하는 형질유전 생쥐 - 최은양 (The Graduate School, Ajou University, 2006)
Tyrosine hydroxylase (TH), the rate-limiting enzyme of catecholamine biosynthesis, is predominantly expressed in several cell groups within the brain, including the dopaminergic (DA) neurons of the substantia nigra and ventral tegmental area. The pathogenesis of some catecholaminergic neuron disorders, such as Parkinson's disease, may be related to changes in TH. To analyze the TH promoter responsible for transcriptional activity during development and dopamine neurogenesis, we produced lines of two transgenic mice carrying 3.2-kb fragments from the 5’-flanking region of the human TH gene and up to exon 3 region from 3.2-kb fragment fused to a reporter gene, enhanced yellow fluorescent protein (EYFP), and designated them as hTHP-EYFP and hTHP-ex3-EYFP, respectively. In this transgenic mice lines, enhanced yellow fluorescent protein allows resolution at the cellular and sub cellular level. In adult stage, hTHP-EYFP transgenic mice show neuron specific EYFP expression in various area such as olfactory bulb, striatum, hippocampus, interpeduncular nu, cerebral cortex, and in particular dentate gyrus. However, few EYFP+ cell co-localized with DAnergic neurons. Granule neuronal cells particularly showed strong EYFP fluorescence, which co-localized with calbindin immunoreactive cells, suggesting that those cells are mature granule cells. However, in hTHP-ex3-EYFP transgenic mice we could not observe any fluorescence, but confirmed the existence of EYFP mRNA using in situ hybridization, suggesting incorrect splicing events of human TH mRNAs may occur in mouse. In addition, EYFP mRNA expression pattern was very similar to hTHP-EYFP mice. But drive gene expression in more tissue-specific manner. All these results suggest that in upstream region 3.2kb of human TH promoter are present regulatory cis-acting elements for tissue-specific TH gene expression over all neuronal development and promoter region longer than 3.2kb and exon-intron sequence may be needed for DAnergic specific expression.
학위논문(석사)--아주대학교 일반대학원 :신경과학기술과정,2006. 2
Keywords: tyrosine hydroxylase; transgenic mice